Environmentally assisted crack growth rate of an austenitic steel TP347HFG in high‐temperature medium. Issue 8 (29th December 2017) - Khan, Hasan Izhar; Zhang, Naiqiang; Yue, Guoqiang; Jiang, Dongfang; Asif, Tahir; Xu, Hong
Abstract : The crack growth rate (CGR) tests of austenitic steel TP347HFG were conducted under <10‐8000 ppb dissolved oxygen (DO) in steam, the alternating environment of air and steam and supercritical water (SCW) at 600–650 °C. A constant stress intensity factor (K) method and direct current potential drop technique were used in the tests to evaluate its environmentally assisted cracking (EAC) properties as superheater and reheater boiler tubes in ultra‐supercritical power plants. CGR increases monotonically with temperature and DO content. CGR in SCW is greater than that in the high‐temperature steam which indicates that exposure pressure has an obvious effect on crack propagation. The varying CGR in different experimental environments show that exposure medium participates in the cracking process. Fracture surface and cross‐sectional surface of compact tension specimen were analyzed by scanning electron microscope. The mechanism of crack propagation in different exposure environment is further discussed. Abstract : Crack growth rate tests of austenitic steel TP347HFG were conducted under <10‐8000 ppb dissolved oxygen in steam, the alternating environment of air and steam and supercritical water at 600–650 °C. A constant stress intensity factor method and direct current potential drop technique were used to evaluate its environmentally assisted cracking properties as superheater and reheater boiler tubes in ultra‐supercritical power plants.